The Importance of Non-Invasive Mechanical Ventilation: Current Status in Iran - Safari, Saeid; Lotfi, Amir Hossein; Hekmatafshar, Mitra (Annals of Anesthesiology and Critical Care, 2016)
Over the past two decades, the use of non-invasive positive pressure ventilation (NIPPV) has increased in many ICUs around the world (1). According to a study conducted in French, the use of non-invasive ventilation during 1994 to 2001 increased from 20 to 90% (2). The result of serial survey from more than 40 countries indicated that the overall use of NIPPV increased from 4.4% in 1998 to 14% in 2010 (3, 4). NIPPV is used in wide variety conditions. It is a wellrecognized approach in the management of acute respiratory failure, acute exacerbations of chronic obstructive pulmonary disease (COPD), hypoxemic respiratory failure, community-acquired pneumonia, cardiogenic pulmonary edema, and after solid organ transplants (5). It is also considered as the most effective treatment available for motor neuron disease when respiratory symptoms appear (6). Non-invasive ventilation is a well-known strategy to avoid endotracheal intubation and its complications (7). Endotracheal intubation in critically ill patients is accompaniedbyhigh riskandlife threatening complications such as severe hypoxemia and hypotension, even in intensive care units (8). NIPPV reduces endotracheal intubation rate, mortality, and length of stay in the intensive care unit and it is a life-saving intervention (9-11).